The Influence of Financial Literacy and Business Inclusion on Business Performance - Yenni Sofiana Tambunan; Ibnu Hajar; Robert Tua Siregar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the influence of financial literacy, financial technology (fintech), and financial inclusion on the sustainability of micro, small, and medium enterprises (MSMEs) with business performance as a mediating variable. A quantitative approach with an explanatory design was applied in this research, where primary data were collected through the distribution of structured questionnaires to MSME owners in Medan City, selected using a purposive sampling method. Data analysis was conducted using Partial Least Squares-Based Structural Equation Modeling (PLS-SEM). The structural model testing results indicate that financial literacy, fintech, and financial inclusion have positive and significant effects on business performance, and business performance is proven to be the most powerful predictor in determining long-term business sustainability. The mediation analysis also shows that business performance is only partly responsible for the link between financial literacy and financial inclusion and business sustainability. At the same time, business performance completely mediates the effect of fintech on business sustainability. This finding underscores that the adoption of fintech technology does not automatically guarantee the immediate survival of MSMEs; rather, it must first be translated into operational efficiency and increased daily business profitability. The primary recommendation for fostering a resilient and sustainable MSME sector is to strengthen internal financial management capacity and expand access to the digital financial ecosystem.